Impacts of Bolsa Família Program on infant health - Bonomo, Tiago Pucheu (2018)
The objective of this dissertation is to evaluate the impacts of the introduction of a cash transfer for pregnant women in the design of the Bolsa Família Program (BFP) on infant health. In particular, I focus on the effects on birth weight and on the incidence of low birth weight, but I also assess the impacts on pregnancy outcomes such as the incidence of preterm births and prenatal care. The new benefit consists of nine monthly transfers which start to be paid when the woman is identified as pregnant by the health management system of the BFP, regardless of the stage of pregnancy at the moment of the identification. The empiracal strategy explores the fact that when the transfer was implemented eligible women at different stages of pregnancy were exposed to different income shocks before giving birth. Using administrative data from the BFP and from the Brazilian Ministry of Health, I create links between benficiary women and their children's natality outcomes. The main results show that the transfer had a positive impact on birth weight and reduced significantly the likelihood of low birth weight. I also find that higher exposures to the transfer during pregnancy reduced the incidence of preterm births. While I don't find significant impacts on the number of prenatal visits, the results show that the transfer reduced the likelihood of delayed prenatal care.